2019
DOI: 10.3889/oamjms.2019.421
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Study of Cutaneous Leishmaniasis in Neyshabur County, East of Iran (2011-2017)

Abstract: BACKGROUND: Cutaneous Leishmaniasis (CL) isn’t a deadly disease, but it has always been taken into consideration due to the long-term involvement of patients with skin. Various factors can play an intervening role in increasing the rate of disease. The present study aimed to evaluate the prevalence and associated factors of disease from 2011-2017 and provide appropriate control strategies for reducing its incidence in Neyshabur county. METHODS: All patients with CL, who had medical records in the health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The results of this study showed that the highest incidence of CL in Ilam province occurred in 2014 (269.6 per 100,000 populations), and the number of infected cases gradually decreased to 133.4 per 100,000 populations in 2017. The downward was shown in previous studies (4,6). The downward trend possibly will be due to interventional measures, such as rodent elimination, general education, or reduction of the population susceptible to Leishmaniasis.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The results of this study showed that the highest incidence of CL in Ilam province occurred in 2014 (269.6 per 100,000 populations), and the number of infected cases gradually decreased to 133.4 per 100,000 populations in 2017. The downward was shown in previous studies (4,6). The downward trend possibly will be due to interventional measures, such as rodent elimination, general education, or reduction of the population susceptible to Leishmaniasis.…”
Section: Discussionsupporting
confidence: 73%
“…The prevalence of Leishmaniasis in Iran is increasing, and annually, the cases of the disease are reported from different parts of the country; main focal regions of wet-type leishmaniasis involve villages of Isfahan, Khuzestan, Ilam, and northeast of Iran while main focal regions of dry-type leishmaniasis involve some big and small cities, such as Mashhad, Tehran, Shiraz, Kerman, Bam, Yazd, and Neyshabur (4,5). According to official reports from the Ministry of Health and Medical Education, the average incidence rate of CL is usually between 20 to 40 per 100,000 populations, and average more than 150 cases per 100,000 population was reported in endemic areas, including Yazd, Semnan, Fars, Ilam, Khuzestan and Isfahan (6).…”
Section: Introductionmentioning
confidence: 99%
“…In Khorasan Razavi province in northeast Iran, CL is prevalent in Torghabeh–Shandiz, Sarakhs, Daregaz, and Neyshabur cities and children in these areas are affected with the disease [ 71 , 130 ]. In Khorasan Razavi, Sabzevar city, children below the age of 4 years in rural areas were demonstrated to have a greater incidence of CL [ 151 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some socio-epidemiological risk factors were identi ed for high incidence in this region, which include density of population, stray dogs, and some cultural and economic factors (13). Some studies also revealed a high frequency of CL in the cities of Neishabour (50) and Torghabeh-Shandiz (16). Both of these cities are located to the west of Mashhad, and these results reinforce the ndings of the present study.…”
Section: Discussionmentioning
confidence: 98%